2019
DOI: 10.32615/ps.2019.044
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of starch content increase in grain of autotetraploid rice (Oryza sativa L.)

Abstract: Net photosynthetic rate (PN), photorespiration (PR), chlorophyll (Chl) content, Chl fluorescence parameters, starch accumulation, and related key enzyme activities were determined during the grain-filling stage in two autotetraploid lines and corresponding diploid rice lines. The results showed that autotetraploid rice lines had a higher Chl content, PN, electron transport rate, maximum photochemical efficiency of PSII, actual photochemical efficiency of PSII, and lower PR in leaves than that in corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Polyploids often show larger stomatal guard cells, larger stomatal openings, a lower stomatal density, and wider xylem conduits. This in turn affects water transport but can do so in opposite directions, providing a positive (Vyas et al 2007, Ntuli and Zobolo 2008, Zhou et al 2015, Dudits et al 2016, Wang et al 2019, Yang et al 2019, Zhang et al 2020), negative (Niu et al 2016), or neutral (Solhaug et al 2016) effect on photosynthetic rates and usually increasing drought resistance (Ntuli and Zobolo 2008, Li et al 2009, van Laere et al 2011, Deng et al 2012, Del Pozo and Ramirez‐Parra 2014, Zhang et al 2015, Rao et al 2020, Jiang et al 2022). Moreover, the increased surface area to volume ratio of larger cells slows down the cell cycle (Cavalier‐Smith 1978, Comai 2005).…”
Section: Immediate Fitness Effects Of Polyploidization: Novel Phenotypementioning
confidence: 99%
“…Polyploids often show larger stomatal guard cells, larger stomatal openings, a lower stomatal density, and wider xylem conduits. This in turn affects water transport but can do so in opposite directions, providing a positive (Vyas et al 2007, Ntuli and Zobolo 2008, Zhou et al 2015, Dudits et al 2016, Wang et al 2019, Yang et al 2019, Zhang et al 2020), negative (Niu et al 2016), or neutral (Solhaug et al 2016) effect on photosynthetic rates and usually increasing drought resistance (Ntuli and Zobolo 2008, Li et al 2009, van Laere et al 2011, Deng et al 2012, Del Pozo and Ramirez‐Parra 2014, Zhang et al 2015, Rao et al 2020, Jiang et al 2022). Moreover, the increased surface area to volume ratio of larger cells slows down the cell cycle (Cavalier‐Smith 1978, Comai 2005).…”
Section: Immediate Fitness Effects Of Polyploidization: Novel Phenotypementioning
confidence: 99%
“…The change of ploidy has an obvious effect on photosynthetic characteristics. Yang et al also found that autotetraploid rice lines had a high photosynthetic capacity and high light-utilization efficiency [91]. In fact, the relationship between ploidy and photosynthetic parameters is very complex.…”
Section: Autotetraploid Ricementioning
confidence: 99%
“…There are four alleles at Wx locus in autotetraploid glutinous rice, so the range of genotypes and phenotypes of hybrids between autotetraploid glutinous rice and non-glutinous rice is much more complex than that of diploid rice. Yang et al researched the mechanism of starch content increase in grain of autotetraploid rice [91]. They found that the activities of ADP-glucose pyrophosphorylase, soluble starch synthase, and starch-branching enzyme in grains of autotetraploid rice lines were higher than those in grains of corresponding diploid rice lines during the grain-filling stage.…”
Section: Autotetraploid Ricementioning
confidence: 99%
“…Indica and japonica autotetraploid hybrid plants produced by colchicine-induced doubling are large, which provides support for increased yields 16 . Compared with diploid rice, Aautotetraploid rice has a higher photosynthetic capacity and light energy use efficiency and more effectively converts photosynthetic products into starch 17 . Chromosome doubling of rice can increase tolerance to drought stress 18 , and chromosome polyploidization induces the expression of genes related to pollen ontogeny, cell metabolism, cell physiology and so forth 19 .…”
Section: Introductionmentioning
confidence: 99%